2015
DOI: 10.5665/sleep.5162
|View full text |Cite
|
Sign up to set email alerts
|

Study of a Novel APAP Algorithm for the Treatment of Obstructive Sleep Apnea in Women

Abstract: Among premenopausal women a novel female-specific autotitrating algorithm (AfH) is as effective as the standard AutoSet algorithm in controlling obstructive sleep apnea (OSA). The new algorithm may reduce flow limitation more than the standard algorithm and achieve control of OSA at a lower (95th centile) pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…A randomized, double-blind, crossover clinical trial found this modality to be as effective as standard continuous PAP. 82 Non-PAP treatments have rarely been studied in the female-specific population. Weight loss has been seen to be more beneficial for males than females based on the fat distribution in the upper airway of males.…”
Section: Treatmentmentioning
confidence: 99%
“…A randomized, double-blind, crossover clinical trial found this modality to be as effective as standard continuous PAP. 82 Non-PAP treatments have rarely been studied in the female-specific population. Weight loss has been seen to be more beneficial for males than females based on the fat distribution in the upper airway of males.…”
Section: Treatmentmentioning
confidence: 99%
“…However, in the female OSA patients, the longest apneas are associated with to a more severe oxygen desaturation [59]. Finally, the female OSA pattern characterized by a significant high percentage of hypopneas and respiratory effort-related arousal (RERA) events [60] has inspired the development of Auto CPAP, working by increasing sensitivity to flow limitation and optimizing the response to these events, with the control of OSA at a lower pressure [61,62].…”
Section: Further Psg/pm Patterns Useful For Clinical Managementmentioning
confidence: 99%
“…One commercially available CPAP device contains an algorithm which aims to address female-specific OSA characteristics. This device was tested in a randomized, double-blind, crossover clinical trial and was found to be as effective as standard CPAP, with a significant reduction in residual flow limitation and lower mean pressures [ 92 ]. An ongoing clinical study is investigating the use of this device on quality of life in women, with outcome measures including daily functioning, sleepiness, depression, sexual function, and sleep quality ( NCT02400073 ).…”
Section: Osa Treatmentmentioning
confidence: 99%